2000
DOI: 10.1007/s004420000414
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for asymmetrical intraguild predation between native and introduced Anolis lizards

Abstract: Since its introduction, Anolis sagrei (Sauria: Polychrotidae) has been replacing native A. carolinensis in Florida and native A. conspersus in Grand Cayman Island as the common anole of urban environments and other open habitats. To assess the likelihood that predation of juvenile native anoles by A. sagrei adults is an important interaction in this process, the propensities for intraguild predation and cannibalism were assessed for A. sagrei and A. carolinensis in Florida and for A. sagrei and A. conspersus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 37 publications
1
27
1
Order By: Relevance
“…For example, within Anolis lizards, A. sagrei has been shown to prey on juvenile A. carolinensis in Florida and A. conspersus in the Grand Cayman (Gerber and Echternacht 2000). Within geckos, predation on juvenile Lepidodactylus lugubris by H. frenatus has been demonstrated experimentally and has been proposed as a potential factor contributing to displacement of L. lugubris (Frogner 1967;Bolger and Case 1992;Case et al 1994).…”
Section: Feeding Plasticity and Opportunity Along An Urban Gradientmentioning
confidence: 99%
“…For example, within Anolis lizards, A. sagrei has been shown to prey on juvenile A. carolinensis in Florida and A. conspersus in the Grand Cayman (Gerber and Echternacht 2000). Within geckos, predation on juvenile Lepidodactylus lugubris by H. frenatus has been demonstrated experimentally and has been proposed as a potential factor contributing to displacement of L. lugubris (Frogner 1967;Bolger and Case 1992;Case et al 1994).…”
Section: Feeding Plasticity and Opportunity Along An Urban Gradientmentioning
confidence: 99%
“…Our literature review shows that cannibalistic preference varies considerably among a wide range of invertebrate and vertebrate predator taxa and can rival or even exceed interspecific predation rates (Gerber and Echternacht 2000;Yasuda et al 2001;Burgio et al 2005;Rudolf 2008). Byström et al (2013), for example, found that freshwater fish often exhibit a strong preference for conspecific relative to heterospecific prey.…”
Section: Cannibalistic Preference and Coexistencementioning
confidence: 99%
“…Search terms were "cannibalistic" or "cannibalism" combined with "preference," "choice," "heterospecific," "interspecific," "Manly's," and "Chesson." Empirical studies: Duelli (1981); Orr et al (1990); Leonardsson (1991); Streams (1992); Macpherson and Gordoa (1994); MacRae and Croft (1997); Baras et al (1999);Schausberger (1999); Walzer and Schausberger (1999) ;Gerber and Echternacht (2000); Schausberger and Croft (2000); Yasuda et al (2001); Gagné et al (2002); Santi et al (2003); Park et al (2005); Dörner et al (2007); Mahe et al (2007); Rudolf (2008); Byström et al (2013). nibalism on both complete diet shift and diet broadening LHIGP scenarios.…”
Section: Model Formulationmentioning
confidence: 99%
“…Symmetrical intraguild predation is uncommon among introduced predators, even when they occupy the same trophic level (Gerber and Echternacht 2000 ). When asymmetry dominates, and both predators have a substantial impact upon the shared prey, a mesopredator release eff ect may occur upon removal of the top predator.…”
Section: Intraguild Predationmentioning
confidence: 99%